Faktor-Faktor yang mempengaruhi Pemasaran Ikan Di Desa Arung Medang Kecamatan Tangaran Kabupaten Sambas - Roujesy Roujesy; Indra Mahyudi S; Beryaldi Agam; Nurul Fatimah Yunita; Maryono Maryono (PAKIS JOURNAL INSTITUTE, 2025)
Arung Medang Village is a coastal area where most residents depend on salted fish processing and marketing as their main source of income. However, the marketing applied by fishermen have not been optimal, resulting in less than maximum income. This study aims to identify the factors that influence salted fish marketing in Arung Medang Village, Tangaran Sub-District, Sambas Regency. The research employed a descriptive quantitative method with a survey approach. The population consisted of 42 salted fish processing fishermen, all selected as respondents using purposive sampling. Data were collected through observation, interviews, questionnaires, and documentation. The data were analyzed using multiple linear regression with SPSS version 26 to examine the effect of the marketing mix (11P) on fishermen’s income. The results showed that simultaneously, all eleven marketing mix variables significantly affected fishermen’s income, with a significance value of 0.043 and a determination coefficient (R²) of 79.4%. Partially, six variables had a significant influence, namely Price, Promotion, Packaging, Promise, Partnership, and Physical Evidence. These findings confirm that such factors are the main determinants of successful salted fish marketing in Arung Medang Village.